Evaluation of Patient-Centered Care (PCC) Implementation at A Type C Private Hospital - Vivi Retno Intening; Ros Eva Simanungkalit; I Wayan Sudarta; Yullya Permina (Universitas STRADA Indonesia, 2025)
Background: Patient-centered care, or PCC, has been recognized as a crucial pillar supporting both patient safety and healthcare quality. PCC must be monitored and evaluated, and reporting or documentation must be used as a communication mechanism. To determine the effectiveness of health care implementation, an assessment system is put in place. Purpose: To evaluate the implementation of PCC at a type C private hospital. Methods: A descriptive analytical design was applied in this study with a population of 385 inpatients. In this study, 97 respondents or 25% of the population participated as samples, chosen through purposive sampling. The instrument used was a questionnaire containing eight PCC indicators, namely patient choice, communication of information and education, coordination of services, moral support, physical comfort, involvement of family and loved ones, continuity and transition, and access to services. Percentage formulas was used in this study. This research has been declared ethically approved with document number 1117.1/RSPWDC/LP/KEPK/VIII/2023. Results: The dimensions of choice appreciation, moral support, physical comfort, continuity and transition, coordination, and integrated patients included in the good category as many as 97 respondents (100%), dimensions of family involvement and the closest people to patients included in the good category as many as 94 respondents (96.9%), and the dimensions of communication, information, and patient education included in the good category as many as 72 respondents (74.2%). Conclusion: The evaluation of the implementation of PCC implementation at a type C private hospital is in the good category.